Ответ(ы) на вопрос:
ж) [latex](15 \frac{1}{2} - 2 \frac{3}{8}) - (5 \frac{5}{6}+6 \frac{3}{4}) + (10 \frac{2}{3}-5 \frac{5}{8}) [/latex] = [latex]15 \frac{1}{2} - 2 \frac{3}{8} - 5 \frac{5}{6} - 6 \frac{3}{4} + 10 \frac{2}{3}-5 \frac{5}{8} = 7 \frac{12-9-20-18+16-15}{24} = 7 \frac{-34}{24} = 6 \frac{-10}{24} [/latex] = [latex]5 \frac{14}{24} = 5 \frac{7}{12} [/latex]
з) [latex](20 - 19 \frac{3}{4}) + (17 \frac{3}{4} - 17) + (2 \frac{1}{2} - \frac{17}{24}) = \frac{1}{4} + \frac{3}{4} + \frac{5}{2} - \frac{17}{24} = [/latex] [latex]1 + \frac{60-17}{24} = 1 \frac{43}{24} = 2 \frac{19}{24} [/latex]
Не нашли ответ?
Похожие вопросы